Key Factors Driving the Adoption of QRIS for Retribution Payments at Domestic Ports in the Riau Islands Province - Nuraisyah, Nuraisyah; Ariyanto, Hepy Hefri; Putra, Edy Yulianto (Dinasti Publisher, 2025)
While research on electronic payment adoption has been explored extensively, an in-depth investigation into the critical factors that motivate ferry passengers to utilize the QRIS application for paying port levies is of utmost importance. This study is important for optimizing levy management processes and enhancing overall efficiency. In our study, we engaged 424 ferry passengers, harnessing an expanded Technology Acceptance Model (TAM) that integrates considerations of compatibility, experience, and technology anxiety. This comprehensive approach enables us to thoroughly evaluate the willingness of passengers to embrace QRIS for their payment needs. Employing the PLS-SEM methodology, our findings reveal compelling insights: both perceived usefulness and perceived convenience play pivotal roles in shaping passengers' attitudes and intentions to adopt QRIS. Notably, while compatibility significantly influences attitudes, it surprisingly does not affect the intention to use the application. Moreover, we found that experience does not sway attitudes or intentions, and while technology anxiety does not significantly affect attitudes but does influence the intention to use QRIS. Crucially, the attitudes towards usage serve as a powerful mediating factor, significantly amplifying the intention to adopt the QRIS application. By understanding these dynamics, we can enhance the implementation of electronic payment systems in ferry operations, ultimately driving greater efficiency and satisfaction among users.